2nd Coatings and Interfaces Web Conference (CIWC-2 2020) 2020
DOI: 10.3390/ciwc2020-06840
|View full text |Cite
|
Sign up to set email alerts
|

NiOOH/FeOOH Supported on Reduced Graphene Oxide Composite Electrodes for Ethanol Electrooxidation

Abstract: In this work, nickel (Ni) and Ni-Fe bimetallic microparticles were electrosynthesized at reduction potentials in the range from −0.70 V to −1.20 V (50 mV s−1) by cyclic voltammetry (CV) onto graphite/paraffin electrode surface modified with nanosheets of reduced graphene oxide (RGO). Previously, the RGO was electrodeposited by CV from a suspension of 1 mg mL−1 of graphene oxide in PBS solution with pH 9.18, in the potential range from −1.50 V to 0.50 V (10 mV s−1). After electrodeposition of metals, the oxyhyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…The mixture of the two did not presented defined shapes, only undefined features. The same situation was reported by Oliveira and collaborators [12,13], but the presence of NiOOH and FeOOH was confirmed by EDX and mapping of elements on the surface of the electrodes.…”
Section: Morphological Characterizationsupporting
confidence: 85%
See 4 more Smart Citations
“…The mixture of the two did not presented defined shapes, only undefined features. The same situation was reported by Oliveira and collaborators [12,13], but the presence of NiOOH and FeOOH was confirmed by EDX and mapping of elements on the surface of the electrodes.…”
Section: Morphological Characterizationsupporting
confidence: 85%
“…Figure 2B shown the cyclic voltammograms of the EC/rGO/NiOOH-FeOOH electrode in the absence and presence of 10 mmol L -1 of methanol and ethanol, the electrode showed an oxidation peak at the potential of 0.57 V for both alcohols and the electrochemical behavior was similar to composite electrode modified with NiOOH. With the addition of FeOOH, the electrodes showed a similar electrocatalytic process of ethanol and methanol in relation to the EC/rGO/NiOOH, however it was observed a shifting in the oxidation potential of ethanol and methanol to a more negative potential, in this case from ~0.66 V to ~0.57 V. Oliveira and collaborators [12] showed that the electrodes modified with only FeOOH in alkaline medium does not shown a electrocatalytic current at the studied potential in presence of alcohols. However, Qiu and collaborators [18] observed that electrodes modified with only FeOOH have a redox potential between −0.60 V and −1.20 V and that the addition of FeOOH can reduce the electrochemical oxidation of Ni(OH)2 in NiOOH, due to the decrease in the amount of active Ni site on the surface, thus the decrease in the amount of electrons transferred by the Ni atom can also be altered.…”
Section: Electrooxidation Of Ethanol and Methanol In Alkaline Mediummentioning
confidence: 82%
See 3 more Smart Citations